2016
DOI: 10.17770/sie2016vol2.1411
|View full text |Cite
|
Sign up to set email alerts
|

Latvian Adaptation of McArthur-Bates Communicative Development Inventories

Abstract: The article discusses the methodology and the preliminary results of the research project entitled “Latvian language in Monolingual and Bilingual Acquisition: tools, theories and applications” (LAMBA). The project involves 25 researchers – linguists, educators, psychologists – from five institutions in Latvia and Norway, and focuses on phonological, lexical and morphosyntactic acquisition of Latvian as a native language in monolingual and bilingual settings. One of the main goals of the project is to develop a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Results showed that parents consistently rated their children's expressive and receptive language skills higher than teachers, particularly in 3-and 5-year-old children, with these differences being statistically significant. This variation in ratings between parents and teachers may be attributed to their differing experiences; teachers compare a child's language proficiency against a broad range of peers, whereas parents might not have such extensive comparative opportunities and may overestimate their children's abilities (Hauerwas & Stone, 2000;Vulane, Taurina, Zirina, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results showed that parents consistently rated their children's expressive and receptive language skills higher than teachers, particularly in 3-and 5-year-old children, with these differences being statistically significant. This variation in ratings between parents and teachers may be attributed to their differing experiences; teachers compare a child's language proficiency against a broad range of peers, whereas parents might not have such extensive comparative opportunities and may overestimate their children's abilities (Hauerwas & Stone, 2000;Vulane, Taurina, Zirina, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the Latvian language adaptation of the MacArthur-Bates Communicative Development Inventories for children aged 8-16 and 16-36 months encountered low parental response rates (8%), attributed to outreach challenges and unequal distribution of parental education levels (Urek et al, 2019). Prior research by Vulane et al indicated that parents' assessments could be overly optimistic or pessimistic, or even superficial, impacting the accuracy of the information provided (Vulane, Taurina, Zirina, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%